Maternal factors affecting outcome of induction of labour - Devarasetty, Shravani; Habeebullah, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Induction of labour is a common procedure in modern obstetrics and accounts for 20% among all deliveries. This study aims to assess the factors associated with success/failure of induction of labour. Methods: This is a cohort study involving 220 women who underwent induction of labour in the department of obstetrics and gynaecology, MGMCRI from December 2016 to May 2018. After obtaining informed consent, patients were recruited into the study. Maternal parameters like age, parity, gestational age, BMI, Bishop score, indication of induction, method of induction, mode of delivery, maternal complications and neonatal parameters like Apgar score, birth weight and NICU admission were analyzed. Association of all parameters with mode of delivery was done by chi square test or Fisher exact test. Results: Out of 220 women who were induced, vaginal delivery rate was 56.4%. Vaginal delivery rate was high in young women of age 20-25 years (65.2%), multiparous women (65.1%), gestational age of > 40-42 weeks (64.7%), with normal BMI (67.7%), with Bishop score ≥ 5(94.6%), induced for PROM and postdates (68.6%) and induced with single agent (74%). Most common indication of caesarean section was fetal distress (43.7%) followed by meconium stained liquor (30.2%). There were no adverse perinatal outcomes. Conclusions: Women of age 20-25 years, normal BMI and induced with single agent showed statistically significant successful induction of labour.